2013
DOI: 10.1002/ejhf.8
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional speckle tracking echocardiography combined with high‐sensitive cardiac troponin T in early detection and prediction of cardiotoxicity during epirubicine‐based chemotherapy

Abstract: Aims To investigate whether alterations of myocardial strain and high‐sensitive cardiac troponin T (cTnT) could predict future cardiac dysfunction in patients after epirubicin exposure. Methods Seventy‐five patients with non‐Hodgkin lymphoma treated with epirubicin were studied. Blood collection and echocardiography were performed at baseline, 1 day after the third cycle, and 1 day after completion of chemotherapy. Patients were studied using echocardiography during follow‐up. Global longitudinal (GLS), circum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 21 publications
(36 reference statements)
3
84
3
1
Order By: Relevance
“…A large study by Khan et al [48], involving 1204 patients, showed 10.2% (n = 123) patients occurred cardiotoxicity which was defined as a reduction in LVEF ≥ 10% absolute points from baseline and LVEF < 55%. Meanwhile, another study with 75 patients reported that 18.67% patients developed an asymptomatic reduction of the LVEF of ≥ 10% after epirubicin therapy [49]. The present results appeared to be discordant with these two studies, however, their patients had received anthracycline > 300 mg/m 2 which were higher than our cumulative dose.…”
Section: Discussionsupporting
confidence: 73%
“…A large study by Khan et al [48], involving 1204 patients, showed 10.2% (n = 123) patients occurred cardiotoxicity which was defined as a reduction in LVEF ≥ 10% absolute points from baseline and LVEF < 55%. Meanwhile, another study with 75 patients reported that 18.67% patients developed an asymptomatic reduction of the LVEF of ≥ 10% after epirubicin therapy [49]. The present results appeared to be discordant with these two studies, however, their patients had received anthracycline > 300 mg/m 2 which were higher than our cumulative dose.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, it has a lower inter-observer variability [39]. In a recent study of non-Hodgkin lymphoma patients, measurements if global longitudinal strain combined with troponin T provided a reliable method to predict cardiac dysfunction in patients receiving anthracycline-based chemotherapy [40]. In our systematically controlled cohort trial, we could also show an impairment of the LV-EF predominantly during chemotherapy.…”
Section: Discussionmentioning
confidence: 84%
“…Whether longitudinal systolic performance precedes the onset of DD (as suggested by smaller studies [41,14]), or whether it is an event that succeeds it -a sign of progression towards systolic heart failure? And what is the predictive value of longitudinal performance impairment for the progression towards heart failure?…”
Section: Discussionmentioning
confidence: 99%